Single-Stage Surgical Correction of Anorectal Malformation Associated with Rectourinary Fistula in Male Neonates - Ernesto Leva; Francesco Macchini; Rossella Arnoldi; Antonio Di Cesare; Valerio Gentilino; Monica Fumagalli; Fabio Mosca; Akbar Bhuiyan; Maurizio Torricelli; Tahmina Banu (EL-Med-Pub, 2013)
Introduction: The treatment of children affected by anorectal malformations (ARM) is characterized by some unsolved problems. The three-stage surgical correction has been known to be most effective in preventing complications, but recently new approaches have been proposed. We describe our experience with the newer approaches. Methods: Twenty three male newborns, affected by ARM and recto-urinary fistula, were treated in 2 different centers in 8 years. Nineteen neonates (birth weight 2.4 - 3.5 kg) received a primary posterior sagittal anorectoplasty (PSARP) at the Department of Pediatric Surgery of the Chittagong Medical College Hospital (group 1). Four term neonates (birth weight 2.9 - 3.4 kg) received a primary pull-through with combined abdomino-perineal approach at the Pediatric Surgery Department of Fondazione Cà Granda of Milan (group 2). Results: Among patients of Group 1, 11 patients had a recto-bulbar fistula and 8 a recto-prostatic fistula. Among the Group 2, 2 had a recto-bulbar fistula and 2 a recto-prostatic fistula. The site of fistula was decided at the time of surgery. In Group 1, 5 post-surgical complications were recorded (26%); 1 child died of sepsis, 3 had dehiscence and 1 stenosis, which resolved with dilatation. In Group 2, the only post-operative complication of small rectal prolapse resolved spontaneously after a few months on follow-up. Group 2 patients were followed-up in a dedicated multidisciplinary colorectal center. Conclusions: Primary repair of ARMs with recto-urinary fistula is a feasible, safe and effective technique in the neonatal period. A combined abdominal and perineal approach seems to guarantee better results. A dedicated team is mandatory, both for the surgical correction and for a long-term follow-up.